PENGARUH INQUIRI-BASED MATHEMATICS EDUCATION DAN GAYA KOGNITIF TERHADAP PRESTASI BELAJAR MAHASISWA PGSD - Diputra, Komang Sujendra (FKIP Universitas Lampung, 2016)
The Effect of Inquiri-Based Mathematics Education and Cognitive Style on PGSD Students’ Academic Achievement. This study aimed to determine the effect of Inquiry-Based Mathematics Education on learning mathematics achievement of PGSD students on Undiksha on Mathematical Subjects with attention to student cognitive style. The study was designed in the form of quasi-experimental with 2×2 factorial design. The population in this study was the second semester students of PGSD Undiksha Academic Year 2015/2016, amounting to 263 students and distributed into groups. Data were collected through mathematics achievement tests which were further analyzed using by Tukey test at the 0.05 significance level. Based on the findings, it can be concluded that the inquiry-based mathematics educationvery effectively applied to students who have the cognitive style of field – independent, and conventional learning effectively applied to students who have the cognitive style of field-dependent. Keywords: Inquiri-Based Mathematics Education, cognitive style,mathematic academic achievement DOI: http://dx.doi.org/10.23960/jpp.v6.i2.201601